The Role of the Resource Teacher: Case Studies in Collaborative Good Practice - O’Donnell, Caroline (REACH: Journal of Inclusive Education in Ireland, 1996)
Resource teachers have the opportunity to develop their role in ways that are supportive, encouraging and empowering to their colleagues who are attempting to meet the special needs of pupils in ordinary classes. Forging collaborative teamwork and helping to focus on agreed specified individualised goals are some of the strategies aimed at sustaining successful integration.